Evaluación del comportamiento mecánico, mediante modelos de plasticidad y fractura, del viaducto en Juliaca – 2024 - Cajia Cajia, Linzes Willi; Torres Yampara, Edgar (Universidad Peruana Unión, 2026)
The present study aimed to evaluate the mechanical behavior of the Juliaca viaduct using nonlinear plasticity and fracture models. The research was conducted under a quantitative approach, with an applied type and explanatory scope, employing a non-experimental design based on numerical simulations using the finite element method. For this purpose, the constitutive model Total Strain Crack Model (TSCM) was used, which allows representing crack evolution and the tension–compression interaction in quasi-brittle materials such as concrete. As a result, the seismic analysis, performed through capacity curves, showed a stable and functional structural behavior. In the X direction, a maximum strength of 265.74 tonf with a displacement of 0.242 m was obtained, while in the Y direction, values of 115.54 tonf and 0.198 m were reached, respectively. Furthermore, the bilinearization of the curves made it possible to identify yield points of dy = 0.0101 m and Vy = 153.44 tonf in X, and dy = 0.0145 m and Vy = 83.57 tonf in Y, with performance displacements lower than the limits established by ASCE 41-23. Maximum strains in steel and concrete remained within the minimal damage range, confirming the absence of significant structural degradation and a predominantly elastic response. In conclusion, the TSCM model proved to be suitable for damage simulation and seismic performance assessment, constituting a reliable tool for structural analysis and maintenance management in concrete bridges.
Keywords: Structural analysis; Mechanical behavior; Fracture models; Plasticity models; Total strain crack model; Viaduct; https://purl.org/pe-repo/ocde/ford#2.01.04